Kontribusi Ekspektasi Kinerja, Usaha, Faktor Sosial dan Fasilitas Terhadap Sikap Operator Sistem Informasi - Krismadinata Krismadinata; Yezi Arnovia; Syahril Syahril; Yahfizham Yahfizham (Jurnal Nasional Teknologi dan Sistem Informasi, 2018)
This article describes acceptance or rejection of the adoption of innovation in the using and utilization of a computer-assisted information system by knowing and revealing the dominant independent variables. They are (X1) asperformance expectation, (X2) as business expectation, (X3) as social factor and (X4) as facility condition factor to dependent variable (Y) as attitude of information system operator. Quantitative approach correlationally with regression analysis method is applied with the population 134 respondents who came from the Local Government Device Unit (SKPD) of Solok City Government. The cluster random sampling technique was employed with 44 respondents. This activities were conducted from November to December 2015. TheLikert scale has been implied to measure a individual behavioral toward something with questionnaires. The results indicates, all the independent variables had a positive influenced on the operator attitude as the user of the information system and the degree of achievement is quite well.